2019
DOI: 10.1111/pbr.12682
|View full text |Cite
|
Sign up to set email alerts
|

Public sector soybean (Glycine max) breeding: Advances in cultivar development in the African tropics

Abstract: Formal public sector soybean breeding in Africa spans over four decades, and it was initiated by the International Institute of Tropical Agricultural (IITA). As the demand of soybean continues to outstrip production, strategic projects such the Tropical Legume (TL) were initiated, in which the main goal was to enhance the productivity of soybean in the farmers' fields in Sub-Saharan Africa. One of the strategies to enhance the productivity of soybean in the farmers' fields is through developing and deploying i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…During the last four decades, soybean lines developed at the IITA (TGx lines) have contributed to a significant increase in soybean productivity and farm income in SSA [12]. Despite the substantial progress in soybean improvement that has occurred over the years, the existence of a narrow genetic base in most of soybean breeding programs, including in the USA, has raised major concerns [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last four decades, soybean lines developed at the IITA (TGx lines) have contributed to a significant increase in soybean productivity and farm income in SSA [12]. Despite the substantial progress in soybean improvement that has occurred over the years, the existence of a narrow genetic base in most of soybean breeding programs, including in the USA, has raised major concerns [28].…”
Section: Discussionmentioning
confidence: 99%
“…Systematic soybean breeding efforts in SSA spans over four decades following the establishment of the International Institute of Tropical Agriculture (IITA), in Ibadan, Nigeria. Consequently, a large number of improved soybean cultivars were developed in collaboration with National Agricultural Research Systems (NARS) for target countries [6,12]. Since soybean is an exotic crop for the SSA, the dependence on IITA soybean materials is not only expected from NARS with small soybean research programs, but the major soybean-producing countries of SSA region also rely upon IITA which acts as a gateway for the introduction of elite genetic stocks from Asia, Australia, and the American continent.…”
Section: Introductionmentioning
confidence: 99%
“…The soybean improvement programme at the International Institute of Tropical Agriculture (IITA), Ibadan, Nigeria, has a soybean collection of more than 1800 accessions, including high-yielding cultivars without information on the extent of their genetic diversity. These accessions have been phenotypically screened for priority traits that include disease resistance, pod shattering tolerance, early and medium maturity, efficient natural nodulation, lodging tolerance and yield improvement (Tefera et al ., 2009; Chigeza et al ., 2019). These authors also reported the release of more than 100 IITA bred soybean varieties by the National Agricultural Research Systems across several countries in SSA, following the screening efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, soybean germplasms from Africa have been reported to have a narrow genetic base, based on phenotypic evidence [ 20 ]. However, less information is available at the molecular level [ 21 ]. A few studies have reported the genetic diversity of soybean accessions from Africa using simple sequence repeats (SSR) [ 11 ], but there is no available information about these accessions based on GBS-SNP markers.…”
Section: Introductionmentioning
confidence: 99%